O discurso político de Marina Silva sob a perspectiva da análise do discurso ecológica - Silva, Lais Carolina Machado e (2017)
The study object of this dissertation is the political discourse of Marina Silva. Political discourse, full of social and ideological values, has become research object of investigation in academia, in various areas: linguistics, anthropology, history, communication, etc. However, after research found that political discourse has never been studied from the perspective of Analysis of Ecological Speech. Thus, the theme of this dissertation arose: the study of political Marina Silva speech from the perspective of Analysis of Ecological Speech henceforth ADE. Marina Silva stood out in 2014 in her campaign because talk about the promotion of a "new policy" as opposed to "Old Policy" for her criticism, which aroused the interest in understanding which direction policy in the speeches of the former candidate. Also in this campaign Marina was considered inconsistent for some changes made in their proposals, which raised more concern in understanding the developments that led to change some issues, for example, LGBT causes. Thus, we have as main objective to analyze the Marina interview in order to understand what is the make political and as can to be seen from de perspective of ADE. We define specific objectives: to describe the effects of sense produced in the speech of Marina Silva; checking for agreement and disagreement between the statements of the candidate in interviews and in his government plan, in relation to the themes education, economy, environment and issues relating to the law of minorities, as well as understanding the interactions that led to possible changes between these speech and, finally, analyze the proposals of Marina, seeking to understand how they aim to build new political stances. We selected as analysis corpus an interview with Marina Silva during the presidential campaign of 2014. As a theoretical framework, we used the analisys ecological of discourses. Thus, we present, at first, the Ecolinguistics with their bases, as well as the categories of analysis and some of his views. Even as theoretical support, we present a discussion of different perspectives to think about politics. Therefore, we bring to discussion the Deep Ecology, the Ecopolitics and ecoética. We use the methodology of ADE (ecometodologia), which is the focus, the crop given field interactions, but without neglecting the whole (GARNER, 2004), is characterized mainly for being a multimethodological discipline (COUTO; ALBUQUERQUE, 2015). It was observed that from the perspective of the Analisys ecological of discourses political make Marina is positive for society to working with the diversity that permeates both the field of politics and the community as a whole, which allows the demands of society are better embraced and providing for protection of the environment.